Analisis Kelayakan lnvestasi pada Usaha Tani Buah Naga Super Red Milik Bapak Khodir di Liang Anggang Banjarbaru - Wahid Siswaluya; Hairin Fajerin; Abdullah Dja'far (Universitas Lambung Mangkurat, 2012)
Super red dragon fruit has 15 years of productive age. Thus, it is necessary to calculate cost and benefit accurately considering the huge investment on its cultivation. To know the feasibility of dragon fruit cultivation in Banjarbaru, investment criteria, ie.: net present value (NPV), Benefit Cost Ratio (BCR) and interest rate of return (/RR), are used. On discount rate 13%, NPV is positive (Rp 8,336,768,965.45), IRR is 20% and 12.19. Thus, the cultivation of super red dragon fruit is feasible